Histological alterations in liver and kidney of Javanese medaka (Oryzias javanicus, Bleeker 1854) exposed to sublethal concentration of herbicide Diuron - Kamarudin, Nur Amiera; Zulkifli, Syaizwan Zahmir; Abdul Aziz, Fatin Zahidah; Ismail, Ahmad (Universiti Putra Malaysia Press, 2019)
Diuron has been substantially used in different parts of the world as an herbicide and as a bioactive ingredient in antifouling paint. However, knowledge on the toxicity of Diuron that could adversely affect non-targeted aquatic organisms, especially fish; is still deficient. Therefore, this study was conducted to determine the possible sublethal effects of phenyl-urea herbicide Diuron at the cellular level of the liver and kidneys of an adult Javanese medaka (Oryzias javanicus), which has been used as the novel model organism. In the present study, histological assessment was carried out using the hematoxylin and eosin (H&E) staining protocol where the samples were preserved in 10% buffered formalin and sectioned into 5 µm thickness. The 210 samples used contained a range of Diuron concentrations comprising 1 µg/L, 50µg/L, 100 µg/L, 500 µg/L and 1000 µg/L; which also included the control treatments. Semi quantitative analysis revealed that liver and kidney tissues exposed at higher concentrations (500 µg/L and 1000 µg/L) showed significantly moderate to severe deformities and mild lesion alterations were already shown even at a lower concentration of Diuron exposure (1.0 µg/L), as compared to the control treatment of dechlorinated water (p<0.05). The most evident and observable severity of the lesions in the liver were due to vacuolation, congestion and nodule necrosis while the kidney showed tubule degeneration, glomerulus shrinkage and hemosiderin. Hence, this study further reinforces the documentary evidence in developing O. javanicus as the novel model organism to represent tropical regions in aquatic toxicological studies. Although the level of Diuron in Malaysia is unthreatening, this emerging hazardous chemical can seriously affect the aquatic ecosystem in later years.